A parcel shape index for use in land consolidation planning - Demetriou, Demetris; See, Linda; Stillwell, John (My University, 2013)
Area shape analysis has been a subject of focus for research in geography and other disciplines for many years. However, existing area shape indices present significant weaknesses for the analysis of land parcels in an agricultural context as they do not measure shape in an appropriate, reliable or explicit manner. This article presents a new parcel shape index (PSI) which integrates six geometric parameters through multi-attribute decision-making, combined with value functions for parameter standardization. The superior performance of the new PSI in relation to three existing indices is demonstrated through a case study area in Cyprus. The methodology can be applied in other contexts aimed at assessing the quality of a particular shape compared to an optimum. © 2013 John Wiley & Sons Ltd.
Keywords: Cyprus; Case-studies; Land consolidation planning; Land parcels; Multi attribute decision making; Performance; Shape indexes; Shape-analysis; Study areas; Value functions